Waste less time on Facebook — follow Brilliant.

algorithm 4

Solve the recurrence an=3an−1−3an−2+an−3for n>2 with a0=a1=0 and a2=1. Solve the same recurrence with the initial condition on a1 changed to a1=1.

Note by Pryhant Kielh
3 years ago

No vote yet
1 vote


Sort by:

Top Newest

First recurrence:

\[a(n)=\frac{1}{2} \left(n^2-n\right)\]

Second recurrence:

\[a(n)=\frac{1}{2} \left(3 n-n^2\right)\] Louie Tan Yi Jie · 3 years ago

Log in to reply


If this is the recurrence

\[a(n) = 3 a(n - 1)- 3 a(n - 2) + a(n - 3)\]

then there are many methods. perhaps the simplest is by using the techniques of experimental math.

Generate the first couple of terms

0, 0, 1, 3, 6, 10, 15, 21, 28, 36, 45, 55, 66,...

if you do not recognize that sequence then take it over to the the OEIS. This is a tremendous online resource available to everyone so why "Rediscover America"

[a_n=\frac{1}{2} \left(n^2-n\right)/] Bobbym None · 3 years ago

Log in to reply

@Bobbym None Sorry, bad latexing: \[a_n=\frac{1}{2} \left(n^2-n\right)\] Bobbym None · 3 years ago

Log in to reply

look easy but actually difficult. hehehe :) Pryhant Kielh · 3 years ago

Log in to reply


Problem Loading...

Note Loading...

Set Loading...